Representasi Perubahan Sosial dalam Kampanye LGBT pada Produk IKEA - Bahruddin, Muh.; Putri Erdiana, Setya; Yuan Yurisma, Dhika (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2024)
Advertisement can be used to campaign on social issues, such as the IKEA’s product campaign on the issue of equality for the LGBT community viewed negatively by the people. This article aims to identify the IKEA attempts to change people's perspective through visual communication. This research uses the theory of structuration and Saussure's semiotic method to interpret signs based on signifiers and signifieds. As a result, the social change represented by IKEA with the theme of equality in American history is a donation communication strategy for the LGBT community, that is vulnerable to suicide, by considering local views and culture.